Rola łódzkich uczelni w rozwoju Łodzi i regionu - Danielewicz, Justyna (The Role of High Education Institution in the Development of Lodz City and Region, 2006)
Human capital is one of the main factors of the local and regional development. Companies, taking localisation decision, very often take under consideration resources of local labour market. Knowledge and skills of people became very important. Łódź is one of the cities in Poland with big concentration of higher education institutions. The aim of this paper is to show the role of these institutions in the development of city and region. The main interest is focused on cooperation of University and Polytechnic with other actors in the city. The author presents good examples of collaboration among schools, industry, medical sectors and local and regional authorities.
Prace Naukowe Akademii Ekonomicznej we Wrocławiu; 2006; nr 1124, s. 398-408